2015
DOI: 10.1093/ee/nvv078
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Degree Day Model for the Development ofBactericera cockerelli(Hemiptera: Triozidae) InfestingSolanum tuberosum

Abstract: Bactericera cockerelli (Sulc) (Hemiptera: Triozidae) is a pest of potato (Solanum tuberosum L.) that vectors the bacterium that putatively causes zebra chip disease in potatoes, 'Candidatus Liberibacter solanacearum.' Zebra chip disease is managed by controlling populations of B. cockerelli in commercial potato fields. Lacking an integrated pest management strategy, growers have resorted to an intensive chemical control program that may be leading to insecticide-resistant B. cockerelli populations in south Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The optimum temperature for survival and development of potato psyllids has been estimated to be between approximately 24°C and 27°C but varies depending on factors such as psyllid life stage and host plant (67,93,133). The lower developmental threshold has been estimated to range from approximately 4°C to 8°C (67,133).…”
Section: Phenologymentioning
confidence: 99%
See 2 more Smart Citations
“…The optimum temperature for survival and development of potato psyllids has been estimated to be between approximately 24°C and 27°C but varies depending on factors such as psyllid life stage and host plant (67,93,133). The lower developmental threshold has been estimated to range from approximately 4°C to 8°C (67,133).…”
Section: Phenologymentioning
confidence: 99%
“…The optimum temperature for survival and development of potato psyllids has been estimated to be between approximately 24°C and 27°C but varies depending on factors such as psyllid life stage and host plant (67,93,133). The lower developmental threshold has been estimated to range from approximately 4°C to 8°C (67,133). As temperatures exceed 30°C, oviposition, egg hatching, and survival decrease substantively, with some variation among studies existing in the intensity of effects (67,93,133).…”
Section: Phenologymentioning
confidence: 99%
See 1 more Smart Citation
“…Adults have well-developed wings and legs, are good fliers, and jump readily when disturbed [ 1 , 17 , 18 ]. The optimum temperature for reproduction and development is 24–27 °C, while temperatures above 31 °C may cause death [ 19 , 20 ]. Henne et al [ 21 ] reported that both B. cockerelli nymphs and adults are cold tolerant: nymphs survived at −15 °C for 24 h, and 50% of adults survived at −10 °C for 24 h. However, the development and survival of B. cockerelli are impacted by the identity of the host plant [ 22 ].…”
Section: B Cockerelli As a Crop Pestmentioning
confidence: 99%
“…Wenninger et al [21] also correlated the population abundance of adults B. cockerelli with the accumulated thermal unit and found the population peak at 1775 • C in late August in the Treasure Valley and at 1498 • C in the Magic Valley in Idaho. Lewis et al [34] suggested integrating accumulated thermal units into the management and control of B. cockerelli and proposed a model that integrates thermal unit to simulate the development of potato psyllid infestation.…”
Section: Bactericera Cockerelli Infection By Zebra Chip Pathogen (Canmentioning
confidence: 99%